THE INFLUENCE OF QUALITY OF SERVICE, COMMITMENT AND QUALITY OF ACCOUNTING INFORMATION SYSTEMS ON COMMUNITY SATISFACTION (Survey in Kalikotes District, Klaten Regency) - Dinar Irfani Sodiq; Hadi Samanto; Sri Laksmi Pardanawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research entitled